The translation and certification of legal text: parliament of the Republic of South Africa as a case study - Mbata, Thobile Philladelphia (School of Languages and Literatures, 2022)
This study looks at the translation process, certification and assent of legislation after it had followed the Parliamentary legislative process as required by the Constitution of the Republic of South Africa and the Joint Rules of Parliament. This was done against the background of the history of South African languages, South African Parliament, legislative framework and the history of legal language translation. The study emphasised the fundamental role played by second-language translation in the legislative process. Even though the indigenous languages are still not awarded an equal status in Parliament, a lot has been done in ensuring that most of the new Bills and Acts are translated into the South African indigenous languages. An overview of translation strategies is highlighted to provide a contextual understanding of the functionalist approach to translation. In terms of legal translation, there is a great need that legal language translators be fully trained in the language of the law to be able to deliver an error-free translated legislation. Through observations and interviews, the study showed that Parliament needs to use all indigenous languages on a rotational basis when translating Bills, Acts and on all itsinternal daily papers to promote equality. Certification in English and one other second language translation will assist in creating a working relationship between legal advisers who draft legislation and translators who translate the drafted Bill. This process can lead to the birth of co-drafting in Parliament. The study found that there is a lack of dedication and vision in interpreting and enforcing the provisions stipulated in the Constitution and the legislation governing languages. Parliament of the Republic of South Africa is used as a case study to shed some light on what is happening in the translation unit and the problems that are faced by non-legal translators when translating legal documents. Recommendations are offered, among others, the need for Parliament to develop a training model that dwells more on the use of plain language in legislative drafting and translation. The study concluded by indicating the importance of working hand-in-hand with tertiary institutions in translator training as this will assist in keeping up with some of the developing trends in the legal language field.